Influence of android-based education on mothers’ knowledge in preventing uterine prolapse - Sultina Sarita; Yustiari Yustiari; Khalidatul Khair Anwar; Syahrianti Syahrianti (Public Health of Indonesia)
Background: Pelvic organ prolapse is a common health problem and affects up to 40% of women who have given birth and are over 50 years old.